Delayed wound healing after forefoot surgery in patients with rheumatoid arthritis. Issue 3 (May 2015) - Ishie, Shinichiro; Ito, Hiromu; Azukizawa, Masayuki; Furu, Moritoshi; Ishikawa, Masahiro; Ogino, Hiroko; Hamamoto, Yosuke; Matsuda, Shuichi
Abstract Objective. To elucidate the systemic and local risk factors and the effect of surgical procedures for delayed wound healing after forefoot surgery in patients with rheumatoid arthritis (RA). Methods. Fifty forefoot surgeries were performed in 39 patients using resection arthroplasty or a joint-preserving procedure (25 feet for each procedure). The associations between the occurrence of delayed wound healing and clinical variables, radiological assessment, or surgical procedures were analyzed. Results. Delayed wound healing was recorded in nine feet of eight patients. The duration of RA was significantly longer in the delayed healing group than that in the healed group. Age, sex, smoking history, concomitant diabetes, and RA medication did not differ between the groups. Radiological evaluation showed significant differences between groups in metatarsophalangeal dorsal flexion angle. The shortened length of the fourth and the fifth metatarsal bones affected the occurrence of the complication. The joint-preserving procedure had significantly less delayed wound healing compared with resection arthroplasty. Conclusions. Preoperative dorsoplantar deformity and perioperative tissue damage can cause delayed wound healing after forefoot surgery in RA patients.